Robust behavioural effects in response to acute, but not repeated, terpene administration in Zebrafish (Danio rerio) - Hamilton, Trevor; Leigh, Shannon; Hamilton, Trevor (My University, 2021)
Terpenes are fragrant aromatic compounds produced by a variety of plants, most notably cannabis and hops. With increasing legalization of cannabis there is a need to better understand the behavioural effects of terpenes and ultimately their therapeutic value. Our study investigated the dose-dependent impact of three terpenes (limonene 0.25, 0.5, 0.75%; β-myrcene 0.001, 0.01, 0.1%; and 0.0001, 0.001, 0.00125% linalool) on zebrafish (Danio rerio) behaviour when exposed both acutely and repeatedly over a 7-day period. Anxiety-like behaviour, boldness, and locomotion were assessed using the open field test and the novel object approach test. In the acute dosing experiment, limonene and β-myrcene exposed groups demonstrated a significant decrease in locomotion, a decrease in anxiety-like behaviour, and an increase in boldness, while linalool treatment groups demonstrated only minor alterations in locomotion. Moreover, repeated exposure to limonene (0.39%) or β-myrcene (0.0083%) for a seven day period did not result in any significant behavioural effects. In conclusion, our study provides support for an anxiolytic and sedative effect in zebrafish in response to acute limonene and β-myrcene exposure that is no longer present after one week of repeated exposure.
Keywords: zebrafish; behavioral neuroscience; terpenes